UMPSA strengthens ties with industry and agencies - Naqiah, Puaad (UMPSA, 2025)
SHAH ALAM, 18 January 2024 – The organisation of the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Friendly Programme with Industry and Agencies has further strengthened friendships and enhanced closer networking between the university and industry.